Depressive symptoms and associated factors among persons with physical disabilities in disability care homes of Kathmandu district, Nepal: A mixed method study. - Prabin Karki; Prasant Vikram Shahi; Krishna Prasad Sapkota; Rabindra Bhandari; Nabin Adhikari; Binjwala Shrestha (Public Library of Science (PLoS), 2023)
Depression is one of the most common mental disorders, affecting 300 million people worldwide and 75% of these occur in low- and middle-income countries. Persons with physical disabilities are vulnerable groups and are more prone to experience depressive symptoms than the general population. This study investigated the prevalence of depressive symptoms and the associated factors among persons with a physical disability. We conducted a concurrent triangulation mixed methods design using Beck's Depression Inventory scale among 162 persons with physical disabilities in the Kathmandu district. In parallel, eight in-depth interviews were conducted with an interview guideline to collect the participants' perceptions and experiences of disability. Both quantitative and qualitative findings were integrated into the results. We found that about 77% of the participants with a physical disability had experienced depressive symptoms. Unemployment status (adjusted odds ratio (AOR) 2.7, 95% confidence interval (CI) 1.0-7.3) and comorbidity (AOR 2.5, 95% CI 1.0-6.0) had a statistically significant association with depressive symptoms. The majority of people with physical disabilities had negative experiences with societal prejudice and coping with their limitations. They were depressed as well as angry over having to stop their careers, education, and possibilities. Nevertheless, they were significantly happier and less sad than in their earlier years of life because of the possibilities, family environment, improved means of subsistence, therapeutic facilities, and supportive atmosphere at disability care homes. The policymakers should focus on preventing comorbidity and providing technical skills to persons with physical disabilities to improve their employment status and promote a healthy lifestyle.